Magnetic Resonance Imaging Findings in Children With Tinnitus. (February 2015) - Levi, Eric; Bekhit, Elhamy K.; Berkowitz, Robert G.
Objective: Tinnitus in adults is generally investigated by contrast-enhanced magnetic resonance imaging (MRI) to rule out the diagnosis of acoustic neuroma. Acoustic neuroma is rare in children and, therefore, the role of MRI in children with tinnitus is unclear. This study was undertaken to determine the value of MRI in the investigation of tinnitus in children. Methods: Retrospective study of children younger than 18 years who underwent MRI for the investigation of tinnitus over a 10-year period. Results: Sixty-five patients were identified, but there were only 34 who had also undergone audiologic assessment. Among the 25 patients with normal audiology, MRI abnormalities were present in 9, but these were all thought to be nonspecific. Nine patients had abnormal audiograms and the MRI was abnormal in 4 of these cases, which included 3 children who were found to have multiple sclerosis. Conclusion: Magnetic resonance imaging would appear to be mandatory in the investigation of tinnitus in children who are found to have sensorineural hearing loss, particularly to rule out the diagnosis of multiple sclerosis. Although our study does not support the routine use of MRI in children with normal audiology, the numbers in our series are too small for a conclusive recommendation.